EFFECT OF FLY ASH ON COMPRESSIVE STRENGTH AND WORKABILITY OF CONCRETE - Suhail Zaffar; Shahnaz Perveen; Raheela Anjum (Spectrum of Engineering Sciences, 2025)
Ordinary Portland cement (OPC) is one of the main ingredients used in concrete production and remains largely irreplaceable in the civil construction industry, despite being a versatile but relatively high-cost material. Large scale cement production causes significant environmental problems, including CO₂ emissions, while also contributing to the depletion of natural resources. This has led researchers to investigate the use of industrial by-products as supplementary cementitious materials in concrete. The main parameter investigated in this study is normal concrete (1:2:4 at 0.5 w/c) with partial replacement of cement by fly ash at 0%, 3%, 6%, 9%, and 12% by weight. This paper presents a detailed experimental study on compressive strength at 7 and 28 days, along with workability. Test results indicate that the use of fly ash in concrete improved performance in both strength and durability, with the highest 28-day compressive strength of 28.55 MPa recorded at 12% fly ash replacement, compared to 21.75 MPa for the control mix.